Pengaruh Model Pembelajaran Cooperative Script Terhadap Keterampilan Membaca Cerita Fiksi Siswa Kelas IV Sekolah Dasar - Putri Suci Wardani; Septi Fitri Meilana (Universitas Negeri Makassar, 2022)
This study has a purpose, namely to find out whether there is an effect of the cooperative script learning model on the fiction reading skills of fourth grade students at SDN Kramat Jati 01. This experimental study was a quasi-experimental type of design, non-equivalent control group design, and used samples in grades IV-A as the control class and class IV-B as the experimental class with saturated sampling technique. This type of research instrument is in the form of a description test. The results obtained from the Normality Test using the Lilifors test formula, in the pretest experimental class obtained Lcount < Ltable = 0.099 < 0.161, pretest in the control class 0.107 < 0.161, posttest experimental class 0.095 < 0.161, posttest in the control class 0.127 < 0.161 so that the stated value data obtained based on all classes normally distributed. Furthermore, the results of the independent t test hypothesis test obtained 0.004 <0.05. It was stated that there was an influence on the cooperative script learning model on the fourth-grade fiction reading skills at SDN Kramat Jati 01.